Identifying High Risk Pregnancy and Its Effectiveness in determining Maternal and Perinatal Outcome - Shrestha, Junu; Gurung, Sangeeta Devi; Subedi, Anjali; Pandey, Chandani (Birat Journal of Health Sciences, 2021)
Introduction: Identification of high risk pregnancy can be done by using various scoring systems which is highly predictive in determining maternal and perinatal outcome. Objectives: The objectives of the study were to identify high- risk pregnancy and to compare the maternal and perinatal outcome of high-risk with low-risk pregnancies. Methodology: This study was conducted in the department of obstetrics and gynaecology, Manipal Teaching Hospital, Pokhara, from 1st August 2020 to 31st January 2021. Study included pregnant women coming for delivery after 28 weeks of gestation. Antenatal scoring system involving various risk factors, was used to stratify women as low-risk (score 0-3), high-risk (score 4-6) and extremely high-risk group ( score ≥7). All women were followed up in intrapartum and postpartum period and complications noted. Neonates were also followed up. Maternal and perinatal outcome of three groups were compared. Results: There were 67.3% women in low-risk, 20% in high-risk and 12.7% in extremely high-risk groups. Operative deliveries were 89.9% in extremely high- risk, 77.9% in high- risk as compared to 51% in low- risk group. Maternal complications, total amount of blood loss and duration of hospital stay was more in extremely high-risk and high-risk pregnancies. Low birth weight was more common in extremely high risk (60%) and high-risk (26%) pregnancies compared to low- risk pregnancies (15%). Neonates with low Apgar scores at 1 and 5 minutes were more in high-risk pregnancies. Thirty-two percent neonates in extremely high-risk pregnancy required neonatal intensive care admission which was significantly higher as compared to high-risk and low-risk pregnancies. Perinatal deaths were more frequent in extremely high-risk pregnancies. Conclusions: Identifying high risk pregnancy using scoring system is useful to identify women at risk of developing maternal and perinatal complications.